River Bedup catchment water level prediction using pre-developed ANN Model of Siniawan catchment - Bustami, R. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study proposes the application of Artificial Neural Network (ANN) in the prediction of hourly water level under tidal influence for Sadong Basin. An ANN is undoubtedly a robust tool for forecasting various non-linear hydrologic processes, including the water level prediction.